Examination schedule notofication using short message service (SMS) / Mohd Nazif Tahir - Tahir, Mohd Nazif (2010)
As a human, forgetfulness is a normal thing that happens in life. Because of busy of working and also the busy in life that make the human is forgetfulness. There are many things that must be remembers. It is same as student, there are many things that must be remember and also will be busy for the tests, examinations, quizzes, assignments, readings and etc. In order to solve the above problem, they must have some kind of technique. There are many techniques that can be used for making reminder. But, it has many dis advantages such as no signal, manual and etc. In the improvement of the technology, there are many solutions that can be used to make the reminder can be used anywhere and anytime such as SMS, WAP and etc. This research proposes the SMS technique in reminder that use push technology.